POLYGENIC EXOGENOUS FORMATION OF URANIUM DEPOITS IN DNIEPER DONETSK DEPRESSION - Рослий, І. (Київський національний університет імені Тараса Шевченка, 2012)
The mechanism of forming of the Adamovskoie, Krasnooskolskoie, Berekskoie poligenous uranium – bitumenous fields being attributed to the local stratigraphical disconformities of the Systems of the Carboniferous and Permian, has been considered. The synchroneity of all the following named – the dynamical activity of fractures, the forming of anticlinal structures, the input of hydrothermic ore – bearing solutions, the destruction of hydrocarbon pools, the forming of U-bitumenous mineralization in hydrogeologically opened structures has been strongly paid attention. The U-bearing metallizations being accompanied by that of polymetallization-present

Розглянуто механізм формування Адамівського, Краснооскольського, Берекського полігенних уран-бітумних родовищ, що відносяться до локальних стратиграфічних неузгодженостей систем карбону та пермі. Особливо приділено увагу синхронності всього наведеного – динамічної активності, тріщинуватості, формування антиклінальних структур, надходження гідротермальних рудоносних розчинів, руйнування вуглеводневих залежів, формування уранового зруденіння в гідрогеологічно відкритих структурах. Присутня U-подібна металізація, що супроводжується поліметалізацією.
ПОЛІГЕННО-ЕКЗОГЕННЕ ФОРМУВАННЯ РОДОВИЩ УРАНУ В ДНІПРОВСЬКО-ДОНЕЦЬКІЙ ЗАПАДИНІ